THE PROBLEMS AND CHALLENGES OF CHILDREN FROM MULTICULTURAL FAMILIES IN SOUTH KOREA - Gyem, Kim Jang (Puitika, 2015)
In this article, the problems and challenges of children from multicultural families in South Korea are described. The research subjects were the children (preschool-elementary school ages) from multicultural families (Korean and Indonesian) who settled in Korea. The objects of this qualitative study are the problems and challenges that they face. The data obtained are described and analyzed and then presented with descriptive methods. The problems faced by the children of multicultural families are generally more to the Indonesian culture. They almost did not get the problems with the Korean social and culture life because they grow and develop in Korean social society and culture. They can overcome some of the differences and difficulties with the help of social institutions provided by the Korean government for multicultural families. Thus, the challenge that they face is to equally understand both of their background cultures, the Korean and Indonesian.Key words: children of multicultural families, Korea, IndonesiaABSTRAKÂ Dalam artikel ini, dideskripsikan mengenai masalah dan tantangan anak-anak dari keluarga multikultural di Korea Selatan. Subjek penelitian adalah anak-anak (usia prasekolahâ€”sekolah dasar) dari keluarga multikural (Korea dan Indonesia) yang menetap di Korea. Objek penelitian kualitatif ini adalah masalah dan tantangan yang mereka hadapi. Data yang didapatkan dideskripsikan dan dianalisis kemudian disampaikan dengan metode deksriptif. Permasalahan yang dihadapi oleh anak-anak dari keluarga multikultural tersebut umumnya lebih kepada budaya Indonesia. Mereka hampir tidak mendapatkan masalah dengan kehidupan sosial budaya Korea karena tumbuh dan berkembang dalam masyarakat sosial dan kebudayaan Korea. Beberapa perbedaan dan kesulitan dapat mereka atasi dengan bantuan lembaga sosial yang disediakan oleh pemerintah Korea untuk keluarga multikultural. Dengan demikian, tantangan yang mereka hadapi adalah memahami dua budaya yang melatarbelakangi mereka, yaitu budaya Korea dan Indonesia secara seimbang.Kata kunci: anak-anak keluarga multikultural, Korea, Indonesia